2016
DOI: 10.1007/s00167-016-4225-8
|View full text |Cite
|
Sign up to set email alerts
|

Early weight bearing versus delayed weight bearing in medial opening wedge high tibial osteotomy: a randomized controlled trial

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 39 publications
1
28
0
1
Order By: Relevance
“…1,2 Some authors have described full-weight bearing as early as 2 weeks post-surgery without negative impact. 3 Tomofix patients tend to resume normal activities of living soon after surgery with work-related physical activities introduced at 3-4 months and sports after approximately 6-12 months. 4,5 One reservation for allowing patients to fully weight bear early on is the perceived risk of loss of correction of the angle, although in practice this effect appears to be a rare occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Some authors have described full-weight bearing as early as 2 weeks post-surgery without negative impact. 3 Tomofix patients tend to resume normal activities of living soon after surgery with work-related physical activities introduced at 3-4 months and sports after approximately 6-12 months. 4,5 One reservation for allowing patients to fully weight bear early on is the perceived risk of loss of correction of the angle, although in practice this effect appears to be a rare occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Darees [18] believes that if TomoFix is used as internal fixation, knee varus does not require bone grafting within 15°, and most of the osteotomy sites can heal by themselves within 1 year. It is currently believed that bone grafting is related to the patient's bone quality, correction angle and internal fixation type [19][20][21]. In this group of studies, the patients had good bone quality and their distraction distance was less than 15mm.…”
Section: Discussionmentioning
confidence: 84%
“…Another study by Hernigou et al (2013) 45 reported no differences in terms of hip-knee-ankle angle, tibial slope, or Caton index. Lansdaal et al 10 and Schröter et al 12 measured the mechanical tibiofemoral angle and found no difference between early and delayed weight-bearing groups. Although the verification methods used differed, most reports show that early weight-bearing does not compromise OWHTO outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have found that immediate weight-bearing was essentially harmless. [10][11][12] Thus, the most appropriate form of postoperative management remains controversial; no consensus protocol has yet been firmly established.…”
mentioning
confidence: 99%
See 1 more Smart Citation